Response of the benthic biomass-size structure to a high-energy submarine canyon - Tung, Chueh-Chen; Chen, Yen-Ting; Liao, Jian-Xiang; Wei, Chih-Lin (Frontiers in Marine Science, 2023)
Body size regulates all biological processes, including growth, reproduction, metabolism, trophic interactions, etc., and is the master trait across organisms, populations, and communities. Despite a rich literature on the impacts of human and natural disturbances on body size, a clear knowledge gap is the effect of the submarine canyons on the benthic size structures in the deep sea, hindering our understanding of the ecological processes of these dominant ecosystems on the continental margin. Therefore, we conducted repeated sediment sampling to compare meiofauna and macrofauna biomass body-size spectrum, growth, metabolism, and size composition from a high-energy submarine canyon, Gaoping Submarine Canyon (GPSC), and the adjacent continental slope off SW Taiwan. The GPSC is a dynamic ecosystem connected to a high sediment-yield small mountain river subjected to strong internal-tide energy, swift bottom currents, frequent mass wasting events, and high terrestrial sediment inputs. We found that the meiofauna and macrofauna were characterized by relatively larger individuals dominating on the slope to smaller ones dominating in the canyon. As a result, the community biomass, secondary production, and respiration were depressed with distinctive biomass-size composition in the canyon compared to the non-canyon slope. The environmental factors related to internal tide disturbance (i.e., bottom current velocity, duration of sediment erosion, or low light transmission) substantially influence the body size composition of the canyon benthos, while food supplies (i.e., TOC and C/N ratio) and sediment characters (i.e., grain size and porosity) correlated closely with the slope communities. We concluded that the disturbed condition in the GPSC may have wiped out or depressed the local benthic assemblages, and only the smaller, more resilient species could persist. Our results also highlight that the alterations of the canyon benthic community could be a reference to deep-sea ecosystems under anthropogenic disturbances or global climate change.